Retrospective analysis of the curative effect of Kanglaite injection on pancreatic cancer - Miao, Xian; Dong, Shu; Zhang, Ling; Wen, Xiaolin; Ruan, Jikai; Qiao, Dawei; Ji, Hongjuan; Cao, Pei; Shen, Shuijie (Journal of Medical Biochemistry, 2025)
Objective To systematically evaluate the curative effect of Kanglaite Injection (KLT) in the treatment of pancreatic cancer (PC) by retrospective analysis. Methods The clinical data of 172 patients with pancreatic cancer were analyzed, and the therapeutic effect, survival time and tumor markers of patients receiving Kanglaite injection combined with conventional chemotherapy were compared with those receiving conventional chemotherapy. Results The univariate results showed that the two groups had WBC, LY#, MO#, NE#, ALB, FFA, CA199, CA125 in age, sex, tumor site, stage of pancreatic cancer, radiotherapy and metastasis, and laboratory indexes. Multivariate analysis showed that the use of KLT in pancreatic cancer patients was significantly related to gender and survival outcome, and KLT could prolong the survival of PC patients. In addition, Chi-square test showed that patients with KLT could reduce the influence on monocyte count and albumin abnormality, which suggested that patients with KLT could reduce the adverse reactions. Conclusion Kanglaite injection combined with conventional radiotherapy and chemotherapy plays a significant role in improving therapeutic effect, improving immune function and prolonging survival expression, and will not increase the incidence of serious adverse reactions. It is a safe and effective comprehensive treatment scheme.
Keywords: Kanglaite injection; Pancreatic cancer; Survival time; treatment effect